Comparison of investment in stocks, gold, and mutual funds before and during the crisis due to the Covid-19 pandemic in Indonesia (Asian Journal of Economics and Business Management, 2023)
Wuhan, China was the epicenter of the virus epidemic known as COVID-19. The developing COVID-19 issue affects the finances of numerous nations, including Indonesia. The government is taking precautions against the spread of COVID-19 by encouraging people to stay home, decrease their movement, avoid crowded places, and add PSBB in 2020 and PPKM in 2021. This study compared the return and risk of stocks, gold, and mutual funds before and after the COVID-19 pandemic, which happened as a result of a crisis occurrence. The data used spans from January 2015 through December 2022 and includes the LQ45 Index's ending price as retrieved from idx.co.id, Antam's gold price as seen on Logammulia.com, and the primary NAV/unit of Manulife mutual funds as seen on Bareksa's official website, Bareksa.com. By using the One-Way ANOVA test followed by the Tukey HSD follow-up test, the result was that before the Covid-19 pandemic there were differences in returns and risks between investment in stocks, gold and mutual funds where before Covid-19 stocks were investments that had the highest returns and risks. Then, It was found that during the pandemic there were differences in returns and risks between stock, gold, and mutual fund investments, with mutual fund investments having the highest return and risk. his research is limited by the fact that only stocks, gold, and mutual funds were examined, with equity mutual fund statistics from Manulife Saham Andalan used for mutual funds. This study focuses on the time of the crisis brought on by the COVID-19 pandemic, but it is anticipated that future studies will be able to incorporate additional investment tools.